Evaluation of atoxigenic isolates of Aspergillus flavus as potential biocontrol agents for aflatoxin in maize - Atehnkeng, J.; Ojiambo, P.S.; Ikotun, T.; Sikora, R.A.; Cotty, P.J.; Bandyopadhyay, Ranajit (Informa UK Limited, 2008)
Aflatoxin contamination resulting from maize infection by Aspergillus flavus is both an economic and a public health concern. Therefore, strategies for controlling aflatoxin contamination in maize are being investigated. The abilities of eleven naturally occurring atoxigenic isolates in Nigeria to reduce aflatoxin contamination in maize were evaluated in grain competition experiments and in field studies during the 2005 and 2006 growing seasons. Treatments consisted of inoculation of either grains in vials or ears at mid-silking stage in field plots, with the toxigenic isolate (La3228) or atoxigenic isolate alone and co-inoculation of each atoxigenic isolate and La3328. Aflatoxin B1þB2 concentrations were significantly (p50.05) lower in the co-inoculation treatments compared with the treatment in which the aflatoxin-producing isolate La3228 was inoculated alone. Relative levels of aflatoxin B1þB2 reduction ranged from 70.1% to 99.9%. Among the atoxigenics, two isolates from Lafia, La3279 and La3303, were most effective at reducing aflatoxin B1þB2 concentrations in both laboratory and field trials. These two isolates have potential value as agents for the biocontrol of aflatoxin contamination in maize. Because these isolates are endemic to West Africa, they are both more likely than introduced isolates to be well adapted to West African environments and to meet regulatory concerns over their use throughout that region.